2017
DOI: 10.1093/jac/dkx367
|View full text |Cite
|
Sign up to set email alerts
|

Safety, tolerability and pharmacokinetics of 21 day multiple oral administration of a new oxazolidinone antibiotic, LCB01-0371, in healthy male subjects

Abstract: LCB01-0371 is well tolerated in healthy male subjects with comparable haematology profiles to placebo, after multiple doses of up to 1200 mg twice daily for 21 days.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Previous experimental evidence showed that, compared with linezolid, delpazolid exhibited superior pharmacokinetic parameters and good safety profiles (14). In a recent clinical trial, Choi and colleagues demonstrated that LCB01-0371 was well tolerated in healthy male subjects after administration of multiple doses of up to 1,200 mg twice daily for 21 days (17). Therefore, the impressive in vitro effectiveness and favorable tolerability of delpazolid make it a promising candidate for use in combination treatment with other anti-TB drugs against MDR-and XDR-TB.…”
Section: Resultsmentioning
confidence: 99%
“…Previous experimental evidence showed that, compared with linezolid, delpazolid exhibited superior pharmacokinetic parameters and good safety profiles (14). In a recent clinical trial, Choi and colleagues demonstrated that LCB01-0371 was well tolerated in healthy male subjects after administration of multiple doses of up to 1,200 mg twice daily for 21 days (17). Therefore, the impressive in vitro effectiveness and favorable tolerability of delpazolid make it a promising candidate for use in combination treatment with other anti-TB drugs against MDR-and XDR-TB.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, delpazolid does not appear to exhibit adverse events associated with repeated dosing. In addition, delpazolid did not cause CYP-mediated metabolism and cardiac repolarisation issues [6,[9][10][11].…”
Section: Safety Evaluation In the Phase 1 Clinical Trial As Pomentioning
confidence: 90%
“…Although the integration of linezolid into RR-TB or MDR-TB treatment can improve outcomes, prolonged administration is often limited by long-term side effects, including reversible myelosuppression, potentially irreversible optic neuropathy, and peripheral neuropathy [5]. Therefore, safety and tolerability are critical issues to consider when prescribing these antibiotics [6]. Less toxic alternatives are under development for diseases that require long-term therapy such as tuberculosis.…”
Section: Linezolid the First Oxazolidinone Antibacterial Agentmentioning
confidence: 99%
“…These results are consistent with the tolerability findings from a recently published Phase I study in which the mean relative changes from baseline of all hematologic values after 21 days of oral LCB01-0371 administration at doses ranging from 800 mg once daily to 1200 mg BID were not significantly different among the doses, including placebo. 20 After a single IV administration, LCB01-0371 exhibited linear pharmacokinetic properties for the range of 200e800 mg regardless of the infusion regimen; t 1/2 , V d , and CL were unchanged over the corresponding dose range, and C max , AUC 0elast , and AUC 0e∞ increased proportionally with increasing IV doses. Similar to these findings, LCB01-0371 after a single PO administration exhibited linear pharmacokinetic properties and dose-proportional systemic exposure over the range of 50e800 mg. 22 However, after a single PO administration of doses >800 mg, a lack of dose proportionality was noted, and CL/F, V d /F, and t 1/2 tended to decrease or increase with increasing doses, suggesting nonlinear pharmacokinetic properties via a saturable absorption or elimination mechanism.…”
Section: Clinical Therapeutics 100mentioning
confidence: 90%
“…Furthermore, in a recently published Phase I study, oral administration of LCB01-0371 at doses ranging from 800 mg once daily to 1200 mg BID for 21 days had no significant effect on any hematologic values. 20 After repeated oral administration, LCB01-0371 is absorbed rapidly within 2 h, and its accumulation on day 7 ranged from 1.10-to 1.46-fold. The elimination t 1/2 was 1.64e1.94 h, which remained unchanged across doses of 400e1600 mg. For patients with comorbidities or signs of moderate or severe disease, conventional treatment of intravenous (IV) antibiotics is initially used.…”
Section: Introductionmentioning
confidence: 99%